The molecular landscape of ASPM mutations in primary microcephaly. Issue 4 (21st November 2008) - Nicholas, A K; Swanson, E A; Cox, J J; Karbani, G; Malik, S; Springell, K; Hampshire, D; Ahmed, M; Bond, J; Di Benedetto, D; Fichera, M; Romano, C; et al.
Abstract : Background: Autosomal recessive primary microcephaly (MCPH) is a model disease to study human neurogenesis. In affected individuals the brain grows at a reduced rate during fetal life resulting in a small but structurally normal brain and mental retardation. The condition is genetically heterogeneous with mutations in ASPM being most commonly reported. Methods and results: We have examined this further by studying three cohorts of microcephalic children to extend both the phenotype and the mutation spectrum. Firstly, in 99 consecutively ascertained consanguineous families with a strict diagnosis of MCPH, 41 (41%) were homozygous at the MCPH5 locus and all but two families had mutations. Thus, 39% of consanguineous MCPH families had homozygous ASPM mutations. Secondly, in 27 non-consanguineous, predominantly Caucasian families with a strict diagnosis of MCPH, 11 (40%) had ASPM mutations. Thirdly, in 45 families with a less restricted phenotype including microcephaly and mental retardation, but regardless of other neurological features, only 3 (7%) had an ASPM mutation. This report contains 27 novel mutations and almost doubles the number of MCPH associated ASPM mutations known to 57. All but one of the mutations lead to the use of a premature termination codon, 23 were nonsense mutations, 28 deletions or insertions, 5 splicing, and 1 was a translocation. Seventeen of the 57 mutations were recurrent. There were no definitive missense mutations found nor was there any mutation/phenotype correlation. ASPM mutations were found in all ethnic groups studied. Conclusion: This study confirms that mutations in ASPM are the most common cause of MCPH, that ASPM mutations are restricted to individuals with an MCPH phenotype, and that ASPM testing in primary microcephaly is clinically useful.